Feasibility and Long-Term Compliance to Continuous Positive Airway Pressure Treatment in Adults With Down Syndrome, a Genetic Form of Alzheimer’s Disease - Giménez, Sandra; Farre, Ariadna; Morente, Fátima; Videla, Laura; Gutiérrez, Marta; Clos, Susana; Fernández, Ana; Blanco, Marta; Altuna, Miren; Pegueroles, Jordi; Asensio, Amparo; Benejam, Bessy; et al. (Frontiers in Neuroscience, 2022)
BACKGROUND: Down Syndrome (DS) is a genetic form of Alzheimer’s disease (AD) with a high prevalence of obstructive sleep apnea (OSA). These characteristics place DS population as an optimal model to study the relationship between sleep and AD and to design clinical trials of preventive sleep therapies for AD. Regrettably, OSA treatment with continuous positive airway pressure (CPAP) is often neglected in adults with DS. In both, clinical practice and research trials, it is usually presumed that these patients will not adapt to or tolerate the therapy. STUDY OBJECTIVE: We aimed to evaluate the feasibility and long term CPAP compliance in this population and their capacity to be enrolled in CPAP research studies. METHODS: We prospectively compared the CPAP compliance of 17 OSA patients with DS and 19 age and sex matched OSA euploid patients. CPAP management and follow-up schedules were prescribed according to the habitual clinical practice. We compared group differences in tolerance, objective and subjective hours of nightly CPAP usage at the 1st, 3rd, 6th, 12th, 24th and 36th month visits. Good compliance was defined as at least 4 hours use per night. We also investigated predictive factors of long term CPAP compliance. RESULTS: The percentage of DS subjects with good CPAP compliance (81.2% vs. 78.9%) and the objective CPAP use (5 vs. 6 hours, p=0.92) did not differ from the control group. Subjective CPAP compliance was significantly higher in OSA patients with DS than in controls in all the follow-up visits (8 vs. 6.75 hours, p=0.001). The DS group had a significantly higher number of visits (9 vs. 5; p=0.021) and mask changes (2.5 vs. 2; p=0.05) than controls. Objective hours of CPAP use at the first follow-up visit predicted long term CPAP compliance (p<0.005). CONCLUSIONS: CPAP treatment is feasible and has good long term compliance in OSA patients with DS. It should be recommended to improve health and prevent comorbidities. DS population is indeed suitable to participate in preventive sleep clinical trials for AD